Safety of tildrakizumab for moderate‐to‐severe plaque psoriasis: pooled analysis of three randomized controlled trials. (4th July 2018) - Blauvelt, A.; Reich, K.; Papp, K.A.; Kimball, A.B.; Gooderham, M.; Tyring, S.K.; Sinclair, R.; Thaçi, D.; Li, Q.; Cichanowitz, N.; Green, S.; La Rosa, C.
Summary: Background: Short‐term interleukin‐23p19 inhibition by tildrakizumab improves plaque psoriasis and appears to be well tolerated. Objectives: Safety and tolerability were assessed for up to 64 weeks of tildrakizumab therapy using pooled data from three randomized controlled trials for moderate‐to‐severe psoriasis. Methods: Data pools for the placebo‐controlled (up to 16 weeks) and full trial periods (up to 64 weeks) were analysed ( n = 2081). Results: In the placebo‐controlled period, frequencies of treatment‐emergent adverse events (TEAEs; range 47·9–54·0%), serious TEAEs (range 1·4–2·3%), discontinuations due to AEs (range 0·6–1·9%), major adverse cardiovascular events (MACEs; range 0·0–0·1%) and severe infections (range 0·0–0·3%) were comparable between tildrakizumab 100 mg, tildrakizumab 200 mg, placebo and etanercept. In the full trial period, exposure‐adjusted rates (patients per 100 patient‐years) for TEAEs, serious TEAEs and discontinuations due to AEs with tildrakizumab 100 mg and 200 mg were lower than or comparable with the placebo rates, and lower than with etanercept. Exposure‐adjusted rates of MACEs (range 0·0–0·5) and severe infections (range 0·9–2·0) were comparable among groups. No TEAEs of inflammatory bowel disease or suicide were reported. Candida skin infections were infrequent at frequencies of 0·1%, 0·3%, 0·0% and 0·0% for the tildrakizumab 100 mg, tildrakizumab 200 mg, placebo and etanercept groups, respectively, in the placebo‐controlled period, and exposure‐adjusted rates of 0·2, 0·7, 0·0 and 0·0, respectively, in the full trial period. Oral candidiasis was also infrequent. Conclusions: Up to 64 weeks of tildrakizumab was well tolerated, with low rates of serious TEAEs, discontinuations due to AEs, and AEs of clinical interest. Abstract : What's already known about this topic? Tildrakizumab improves moderate‐to‐severe plaque psoriasis and appears to be well tolerated with short‐term use. What does this study add? Pooled analysis of three randomized controlled trials consolidates the safety and tolerability in a larger group of patients for up to 64 weeks of tildrakizumab treatment. Linked Comment:  Cline and Feldman. Br J Dermatol 2018;179 :556–557 . Respond to this article